Suitability of the native woody species of the Chaco region, Argentina, for use in dendroecological studies of fire regimes - Bravo, Sandra (2008)
The Chaco region is one of the most extensive areas of dry forests and savannas in South America and fire plays a major role in its ecology. We studied the types of wounds caused by fire on the native woody species of Chaco and evaluated their suitability for fire dendroecological studies. The selected species were “quebracho colorado santiagueño” (Schinopsis lorentzii (Griseb). Engl.), “quebracho blanco” (Aspidosperma quebracho-blanco Schlecht), “algarrobo blanco” (Prosopis alba Griseb), “algarrobo negro” (Prosopis nigra (Griseb.) Hieron), “tusca” (Acacia aroma Gill. Ex Hook. et Arn.) and “garabato” (Acacia furcatispina Burkart). Sampling sites were spread across different locations in the Province of Santiago del Estero, Argentina. A selection was made of individual trees with external signs of fire. Cross-sections of boles and branches were taken from each tree at heights of 0.3 and 1.3 m from the ground. The types of wounds were classified according to the percentage of damaged bole perimeter and the patterns of growth interruption. Species suitability for dendroecological studies was based on longevity, patterns of annual ring growth, type of wound, bark thickness and difficulty in dating the fire event. Two types of wound were studied: fire scars and fire marks. It was determined that S. lorentzii, A. quebracho-blanco, P. alba and P. nigra are the most suitable for dendroecological studies since their longevity and thicker bark development enable them to survive in moderate to high intensity fires. Prosopis and Acacia species have better tree ring demarcation and therefore provide more certainty in fire event dating. Despite the lower longevity and higher susceptibility to fire damage of the Acacia species, they are suitable for dendroecological studies that require analysis over a few decades in environments with lower intensity fire regimes. The distribution areas of the studied species means that they can be used for dendroecological studies of fire in the Western, Eastern and Mountain Chaco areas and the phytogeography provinces of Monte and Espinal.